"Bureaucracy & Beliefs": Assessing the barriers to accessing opioid substitution therapy by people who inject drugs in Ukraine. (June 2015) - Bojko, Martha J.; Mazhnaya, Alyona; Makarenko, Iuliia; Marcus, Ruthanne; Dvoriak, Sergii; Islam, Zahedul; Altice, Frederick L.
Abstract Aims: Opioid substitution therapy (OST) is an evidence-based HIV prevention strategy for people who inject drugs (PWIDs). Yet, only 2.7% of Ukraine's estimated 310, 000 PWIDs receive it despite free treatment since 2004. The multi-level barriers to entering OST among opioid-dependent PWIDs have not been examined in Ukraine. Methods: A multi-year mixed methods implementation science project included focus group discussions with 199 PWIDs in five major Ukrainian cities in 2013 covering drug treatment attitudes, beliefs, knowledge and experiences with OST. Data were transcribed, translated into English and coded. Coded segments related to OST access, entry, knowledge, beliefs and attitudes were analyzed among 41 PWIDs who were eligible for but had never received OST. Findings: A number of programmatic and structural barriers were mentioned by participants as barriers to entry to OST, including compulsory drug user registration, waiting lists and limited number of treatment slots. Participants also voiced strong negative attitudes and beliefs about OST, especially methadone. Their perceptions about methadone's side effects as well as the stigma of being a methadone client were expressed as obstacles to treatment. Conclusions: Despite expressed interest in treatment, Ukrainian OST-naïve PWIDs evade OST for reasons that can be addressed through changes in program-level and governmental policies and social-marketing campaigns. Voiced OST barriers can effectively inform public health and policy directives related to HIV prevention and treatment in Ukraine to improve evidence-based treatment access and availability.